Estudo da inativação fotodinâmica de Escherichia coli em água utilizando azul de metileno e rosa de bengala - Santos, Renata Oliveira (2014)
This work aimed to develop a procedure for disinfecting water by photodynamic inactivation of microorganisms and subsequent removal of photosensitizers. The Escherichia coli photoinactivation was performed using PHLS (Policromatic Halogen Light System) light system irradiation, Methylene Blue and Rose Bengal as photosensitizers, cationic and anionic dyes , respectively. The phase separation between the photosensitizers and the analyzed sample was studied by coagulation, being used the crushed seeds of Moringa oleifera, Chitosan powder and commercial Aluminum Sulphate. All experiments were performed previously in samples of E. coli (ATCC 25922) prepared with a turbidity of about 01 on the Mac Farland scale and later in a sample of effluent from the Sewage Treatment Plant of Uberlândia - MG. The results were quite significant as much photoinactivation as the photosensitizers removal, being Moringa oleifera the best coagulant used, able to remove, from effluent sample, 96.9% Rose Bengal and 75.9% Methylene Blue, both at a concentration of 3,91x10-5 mol L-1.